2021
DOI: 10.3390/ijerph18094783
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Uptake of Breastfeeding: The Role of Early Promotion in the Maternity Hospital

Abstract: Background: This study aimed to explore the prevalence of breastfeeding at birth points in Sicily and the relevance of the factors influencing the adoption of exclusive breastfeeding during hospitalization linked to childbirth. Methods: A survey was conducted to monitor the prevalence of breastfeeding in seven out of nine facilities providing maternity services in the province of Catania (Sicily, Southern Italy) in the years 2016–2018. An online questionnaire was administered using an electronic tablet by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
(59 reference statements)
1
8
0
Order By: Relevance
“…When it comes to private maternity hospitals, they usually ensure the presence of a lactation consultant and the intervention of a psychologist, who support mothers in the postnatal period to initiate the care and breastfeeding of the child [39]. Indeed, it has been described in the literature that the more support mothers receive from maternity staff during the first days after childbirth, the better the likelihood for exclusive prolonged breastfeeding [37,40].…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to private maternity hospitals, they usually ensure the presence of a lactation consultant and the intervention of a psychologist, who support mothers in the postnatal period to initiate the care and breastfeeding of the child [39]. Indeed, it has been described in the literature that the more support mothers receive from maternity staff during the first days after childbirth, the better the likelihood for exclusive prolonged breastfeeding [37,40].…”
Section: Discussionmentioning
confidence: 99%
“…Postcesarean section mothers experience two times more obstacles in exclusive breastfeeding than postvaginal delivery mothers. (13,(41)(42)(43) The proportion of breastfeeding initiation in post-cesarean section mothers ranges from 4.8% to 40.1%. (44,45) Generally, newborns are kept separate from the mothers after cesarean section; hence, early initiation of breastfeeding is delayed.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated infants rooming in with mother encourages initiation of the infant being fed breastmilk, and rooming-in is recommended by numerous public health and clinical organizations to support breastfeeding [1,16,17,18,19]. While early recommendations included consideration for temporary separation of mothers with COVID-19 from their newborns, multiple studies have now found low incidence of SARS-CoV-2 infection among infants born to people with SARS-CoV-2 infection [20] and low risk of transmission from mother to infant when appropriate IPC is followed [21].…”
Section: Discussionmentioning
confidence: 99%